(untitled) - McDonald, Brian Thomas (Hoboken, N.J., 2006)
This practical guide to the business side of landscape design helps minimize errors and improve both productivity and profits. Developed specifically for landscape architects, Landscape Design Documentation includes detailed plan checking, quality control information, case studies and tools for every aspect of the business, including company structure, design process, data collection, construction, closeout, and more. This indispensable book and CD-ROM package is ideal whether youre a professional in landscape architecture, architecture, or urban planning; studying for the Landscape Architecture Registration Exam; enrolled in a professional practice, design, and construction course; or part of an agency or firm working with landscape architects.
Keywords: Landscape design; Quality control